Innovation in Risk Management process in Higher Learning Institution / Marziana Madah Marzuki ... [et al.] - Marzuki, Marziana Madah; Abdul Wahid, Khalid; Mohamad Rosman, Mohamad Rahimi; Mohd Zawawi, Mohd Zafian (2019)
Risk management has been identified as a mechanism to help the organizations to proactively manage risk and monitoring in a continue and conscious way the risks associated with their organization strategic objectives. Nevertheless, the traditional implementation of risk management process has become an issue as there is no effective communication to all parties concerned, ranging from describing those risks that affect firm’s strategies and the actions ultimately taken by the management to minimize the risk failures. The purpose of this study is to propose electronic risk management system that can help the organizations to implement risk management process which starting from identifying risks till monitoring it to ensure that the organizations can minimize the risks and leverage on the emerging risk opportunities. We first investigate the disruption factors of the traditional risk management process We then integrate the risk management process into electronic risk management system known as E-RMS The developed system provides an efficient risk management process for preventing risk identified in an organisation and evaluating the added value of the risk mitigation actions. The findings of the case study shows that the system performance can be improved using E-RMS and the overall risk management time can be reduced by alertness system built in the E-RMS. This system can help the organizations to manage their risk efficiently and eventually help them to achieve their strategic objectives.